2007
DOI: 10.1007/s11027-006-9058-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of carbon leakage in multiple carbon-sink projects: a case study in Jambi Province, Indonesia

Abstract: Abstract. Rehabilitation of degraded forest land through implementation of carbon sink projects can increase terrestrial carbon stock. However, carbon emissions outside the project boundary, which is commonly referred to as leakage, may reduce or negate the sequestration benefits. This study assessed leakage from carbon sink projects that could potentially be implemented in the study area comprised of eleven sub-districts in the Batanghari District, Jambi Province, Sumatra, Indonesia.The study estimates the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Next, Figure 4 shows the reduced emission in the agriculture and livestock management by 2030 with a share of countermeasures. Total reduced CH 4 and N 2 O emissions reached 47 MtCO 2 /year in 2030, which was a much smaller than that in the land use sector. High-efficiency fertilizer application (i.e., split fertilization) on cropland soils, water management in rice paddies and livestock' manure management contributed substantially to reducing emissions in the sectors.…”
Section: Carbon Emission Reduction: Key Land-based Optionsmentioning
confidence: 86%
See 1 more Smart Citation
“…Next, Figure 4 shows the reduced emission in the agriculture and livestock management by 2030 with a share of countermeasures. Total reduced CH 4 and N 2 O emissions reached 47 MtCO 2 /year in 2030, which was a much smaller than that in the land use sector. High-efficiency fertilizer application (i.e., split fertilization) on cropland soils, water management in rice paddies and livestock' manure management contributed substantially to reducing emissions in the sectors.…”
Section: Carbon Emission Reduction: Key Land-based Optionsmentioning
confidence: 86%
“…The INDC [1] shows that Indonesia has taken significant steps to reduce emissions from these land use sectors by reducing deforestation and forest degradation and restoring ecosystem functions and sustainable forest management, including social forestry through active participation of the private sector, small and medium enterprises, civil society organizations, local communities and the most Several studies have addressed potential future land use mitigation efforts in the land use sector of Indonesia by examining several types of specific countermeasures. However, some of these studies used static methodologies based on marginal abatement cost curves [2][3][4][5] without considering changes in mitigation effects or countermeasure costs over time. In addition, other studies estimated historical GHG emissions from peat decomposition, peat fires and forest fires [6][7][8][9][10], but did not evaluate the mitigation potential and cost of peatland area and fires [11] in agriculture and land use sectors containing peatland, considering changes in mitigation effects and countermeasure costs over time.…”
Section: Introductionmentioning
confidence: 99%
“…The main criteria for selection were that a quantitative method was presented, thus excluding qualitative and analytical approaches, and that carbon leakage was explicitly addressed. This resulted in a final list of eight quantitative leakage quantification methods, four addressing secondary leakage [18,[23][24][25] and four addressing primary leakage [26][27][28][29]. (Detailed bibliography and description in the Electronic Supplementary Information, ESI 1).…”
Section: Leakage Methods Described In the Scientific Literaturementioning
confidence: 99%
“…The peer-reviewed method by Boer et al [28] uses a logistic model to estimate the probability of a land use being converted to other uses. They use several predictor variables such as proximity to the project area, distance to transportation channel, area of agricultural land, employment situation, population density and income to establish probabilities of land use change.…”
Section: Primary Leakage Approach 2: Leakage From Agricultural Activimentioning
confidence: 99%
“…In some cases, high levels of leakage have been demonstrated. For instance, Boer et al (2007) studied forestation projects in the Jambi province of Indonesia and found that reductions in C stock due to leakage exceeded gains in C stock linked to forestation over a 10-year period. Other forestation projects showed lower leakage, and worldwide, an average percentage of about 50% leakage seems to be associated with forestation projects (Sathaye and Andrasko 2007).…”
Section: Virtual Biofuelsmentioning
confidence: 99%